Elaboration of CaLa2S4 transparent ceramics from novel precursor powders route. Issue 8 (1st June 2017) - Merdrignac-Conanec, Odile; Durand, Guillaume; Walfort, Sebastian; Hakmeh, Noha; Zhang, Xianghua
Abstract: A cost-effective processing route for the production of calcium lanthanum sulfide CaLa2 S4 (CLS) via a novel fast fabrication of precursor powders is reported. The sinterability of the newly developed powders was investigated by use of Hot-Pressing and pressureless sintering. Complementary techniques (XRD, SEM-EDS, chemical analysis, SSA, FT-IR spectroscopy) were employed to correlate the sintering processes and parameters to the microstructural/compositional developments and optical performances of the densified ceramics. Dense (>99.8% theor.) and homogeneous CLS ceramics were produced by pressureless sintering at 1250 °C for 12 h in H2 S followed by hot-pressing at 1000 °C for 6 h in a powder bed to prevent sulfur loss. Transparency free of impurity absorption has been achieved in the LWIR region (optical transmission of 51% in the 12–14 µm range).